Effects of Partial-body Cryotherapy (− 110°C) on Muscle Recovery between High-intensity Exercise Bouts - Ferreira-Junior, J. B.; Bottaro, M.; Vieira, C. A.; Soares, S. R. S.; Vieira, A.; Cleto, V. A.; Cadore, E. L.; Coelho, D. B.; Simoes, H. G.; Brown, L. E. (International Journal of Sports Medicine, 2014)
The aim of this study was to evaluate the effects of a single partial-body cryotherapy bout between training sessions on strength recovery. 12 young men (23.9±5.9 years) were randomly exposed to 2 different conditions separated by 7 days: 1) Partial-body cryotherapy (subjects were exposed to 3 min of partial-body cryotherapy at − 110 °C between 2 high-intensity training sessions); 2) Control (subjects were not exposed to partial-body cryotherapy between 2 high-intensity training sessions). Subjects were exposed to partial-body cryotherapy after the first training session. The 2 knee extension high-intensity training sessions were separated by a 40-min rest interval. Knee extension training consisted of 6 sets of 10 repetitions at 60°.s−1 for concentric actions and 6 sets of 10 at 180.s−1 for eccentric actions. The decrease in eccentric peak torque and total work was significantly (p<0.05) less after partial-body cryotherapy (5.6 and 2%, respectively) when compared to control (16 and 11.6%, respectively). However, the decrease in concentric peak torque and total work was not different (p>0.05) between partial-body cryotherapy (9.4 and 6.5%, respectively) and control (7.5 and 5.2%, respectively). These results indicate that the use of partial-body cryotherapy between-training sessions can enhance eccentric muscle performance recovery.
Keywords: peak torque; total work; training session recovery; recovery modality; muscle performance